2022
DOI: 10.3389/or.2022.10568
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB Signaling in Tumor Pathways Focusing on Breast and Ovarian Cancer

Abstract: Immune disorders and cancer share a common pathway involving NF-κb signaling. Through involvement with GM-CSF, NF-κB can contribute to proliferation and activation of T- and B- cells as well as immune cell migration to sites of inflammation. In breast cancer, this signaling pathway has been linked to resistance with endocrine and chemotherapies. Similarly, in ovarian cancer, NF-κB influences angiogenesis and inflammation pathways. Further, BRCA1 signaling common to both breast and ovarian cancer also has the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 113 publications
0
10
0
Order By: Relevance
“…In a recent finding, Monica et al reported the involvement of the NF-κB pathway towards resistance to endocrine and chemotherapies in breast cancer [108]. Furthermore, BRCA1 signalling, which is one of the prominent pathways activated in various cancer types including breast cancer and ovarian cancer, additionally possesses the capability to induce the NF-κB pathway [109].…”
Section: Nf-κb: One Of the Key Factors Linking Inflammation In Cancermentioning
confidence: 99%
“…In a recent finding, Monica et al reported the involvement of the NF-κB pathway towards resistance to endocrine and chemotherapies in breast cancer [108]. Furthermore, BRCA1 signalling, which is one of the prominent pathways activated in various cancer types including breast cancer and ovarian cancer, additionally possesses the capability to induce the NF-κB pathway [109].…”
Section: Nf-κb: One Of the Key Factors Linking Inflammation In Cancermentioning
confidence: 99%
“…Dysregulated NF‐κB signaling has been implicated in the development of many human cancers. IκB proteins control NF‐κB activity (Devanaboyina et al, 2022). When inactive, NF‐κB complexes reside in the cytoplasm and bind to IκB.…”
Section: Targeting Bcl‐2 Family Proteins At the Transcriptional And P...mentioning
confidence: 99%
“…In response to ionizing radiation, HER2 overexpression increases the activity of the PI3K/Akt pathway, which activates NF-κB and up-regulates pro-survival genes including manganese superoxide dismutase (MnSOD), cyclin B1, and HER2 [ 67 ]. Moreover, HER2 can mediate the stimulation of the canonical NF-κB, then subsequently mediates the formation and maintenance of the EMT [ 68 ]. The initiation of EMT involves the induction of numerous transcription regulators, including the Smad-interacting proteins ZEP-1/ZFHX1A, ZEB-2/ZFHX1B, SLUG, SIP1, and TWIST1 by the RelA molecule [ 68 ].…”
Section: Nf-κb In Bcmentioning
confidence: 99%
“…Moreover, HER2 can mediate the stimulation of the canonical NF-κB, then subsequently mediates the formation and maintenance of the EMT [ 68 ]. The initiation of EMT involves the induction of numerous transcription regulators, including the Smad-interacting proteins ZEP-1/ZFHX1A, ZEB-2/ZFHX1B, SLUG, SIP1, and TWIST1 by the RelA molecule [ 68 ]. Likewise, estrogen increases the transcription of IKK-α , ERs , and steroid coactivator 3 (SRC3) by binding to a particular area on the cyclin D1 promoter.…”
Section: Nf-κb In Bcmentioning
confidence: 99%
See 1 more Smart Citation